Enhancing uric acid electrochemical detection with copper ion-activated mini protein mimicking uricase within ZIF-8: response surface methodology (RSM) optimization - Abdul Aziz, Siti Fatimah Nur; Hui, Ong Sin; Salleh, Abu Bakar; Normi, Yahaya M.; Yusof, Nor Azah; Ashari, Siti Efliza; Alang Ahmad, Shahrul Ainliah (Springer, 2024)
This study aims to investigate the influence of copper(II) ions as a cofactor on the electrochemical performance of a biocomposite consisting of a mini protein mimicking uricase (mp20) and zeolitic immidazolate framework-8 (ZIF-8) for the detection of uric acid. A central composite design (CCD) was utilized to optimize the independent investigation, including pH, deposition potential, and deposition time, while the current response resulting from the electrocatalytic oxidation of uric acid was used as the response. The statistical analysis of variance (ANOVA) showed a good correlation between the experimental and predicted data, with a residual standard error percentage (RSE) of less than 2 for predicting optimal conditions. The synergistic effect of the nanoporous ZIF-8 host, Cu(II)-activated mp20, and reduced graphene oxide (rGO) layer resulted in a highly sensitive biosensor with a limit of detection (LOD) of 0.21 μM and a reproducibility of the response (RSD = 0.63). The Cu(II)-activated mp20@ZIF-8/rGO/SPCE was highly selective in the presence of common interferents, and the fabricated layer exhibited remarkable stability with signal changes below 4.15 after 60 days. The biosensor’s reliable performance was confirmed through real sample analyses of human serum and urine, with comparable recovery values to conventional HPLC.